The Vocation of Anglican theology - McMichael, Ralph, ed. (London : SCM Press, 2014)
The Vocation of Anglican Theology presents a contemporary Anglican theology rooted in its sources but reaching into the future. A range of leading Anglican theologians, including Rowan Williams, Ellen Charry, Kenneth Stevenson, Mark Chapman and Kathryn Tanner, reflect on key theological subjects such as Christology, ecclesiology and eschatology.
Eschatology/ Christopher A. Beeley
Includes bibliographical references and index.
Keywords: Anglican Communion -- Doctrines; Theology -- Methodology; Pastoral theology -- Anglican Communion